COMPOSITION AND ANIMAL PREFERENCE FOR PLANTS USED FOR GOAT FEEDING IN SEMIARID NORTHEASTERN MEXICO - R. Foroughbakhch; J. L. Hernández-Piñero; A. Carrillo-Parra; A. Rocha-Estrada (Journal of Animal and Plant Sciences, 2013)
Arid and semiarid zones of Northeastern Mexico are characterized as regions with high variation in their climatic conditions but rich in drought-tolerant botanical species which are potentially useful for grazing and pastoral activities. Feeding habits and voluntary intake from a total of 100 grazing goats were determined through identification of the plants that make up their diet, their availability in the rangeland, preference index, browsing height and their chemical composition during a 10-month growing period. Four heights of browsing were determined in the different vegetative strata. Climatic factors were determinant in the height of grazing and the availability of forage. Shrub species constituted 78% of the animal diet during the growing season followed by herbs (12-18%) and grasses (6-10%). The species with higher index of preference offered high availability in the rangeland with proper content of crude protein (10.7-24%), crude fiber (12.2-24.5%), cellulose (5.9-20.6%) and nitrogen free extract (30.2-50.6%). These results indicate that in seasons of high feed availability the intake of most preferred shrubs is taking place most of the time at a browsing height between 80 and 120 cm with species rich enough in nutrients to satisfy their minimum daily protein and fiber requirements. [¿Y que ónda con aquello de que cuando hay muchas hierbas abajo prefieren comer esas hierbas?]Thus, the pasture conditions, climate and the availability of the vegetation in a given season are crucial factors for suitable livestock management.
Keywords: Feed habits; feed intake; shrubs; fodder; chemical composition